Thin Film Composite Hollow Fiber Membrane for Separation in Biorefinery - Elfira, Anuar; Syed Mohd Saufi, Tuan Chik; Mazrul Nizam, Abu Seman; Hafizuddin, Wan Yussof; Ahmad Fauzi, Ismail (AIDIC Servizi, 2017)
One of the newest applications of the membrane technology is for the separation of sugar component and inhibitor removal during biomass processing in biorefinery. Most of the membranes used in biorefinery were commercially purchased and not specifically customise for the biomass hydrolysate processing. In the current study, a series of thin film composite (TFC) hollow fiber membranes were fabricated to tailor the performance toward xylose/glucose refinement and acetic acid removal in biomass processing. Polysulfone (PSf) hollow fiber membrane support was prepared using 20wt% PSf, 2wt% Polyvinylpyrrolidone K30(PVP K30) and 78wt% dimethylformamide (DMF) through dry/wet spinning process. Three types of aqueous monomers were studied in interfacial polymerization process, which are piperazine (PIP), triethanolamine (TEOA) and polyethyleneimine (PEI). TFC hollow fiber membrane prepared using TEOA monomer showed the best performance for separation of biomass hydrolysate component. It exhibited rejection value 50.98  4.11 % of xylose, 71.72  3.92 % of glucose and 5.45  1.93 % of acetic acid. This is corresponding to the ideal separation factor of 1.75  0.10 for xylose/glucose, 3.42  0.54 for acetic acid/glucose and 1.95  0.20 for acetic acid/xylose.